1965
DOI: 10.1136/bmj.2.5474.1349
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of blood loss and fluid balance in paediatric adenotonsillectomy.

Abstract: Attention has recently been drawn to the importance of assessing blood loss in paediatric surgery (Brit. med. 7., 1964), but little has been written about such loss in adenotonsillectomy (Shalom, 1964). In this investigation we have set out to measure the operative blood loss and the degree of pre-operative fluid depletion; the significance of these with regard to postoperative progress is discussed. The opportunity was also taken to compare the effects of two different anaesthetic sequences on the operative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

1966
1966
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 4 publications
1
1
0
2
Order By: Relevance
“…So, age in children and the blood loss is not significant and patient's age doesn't have an impact on adenotonsillectomy blood loss. This finding correlates with Holden and Maher's [2] and Shalom's [13] study on blood loss measurement. In a study conducted by KC Prasad and SC Prasad [1], it was shown that the older the child is, the greater the blood loss is.…”
Section: Discussionsupporting
confidence: 76%
“…So, age in children and the blood loss is not significant and patient's age doesn't have an impact on adenotonsillectomy blood loss. This finding correlates with Holden and Maher's [2] and Shalom's [13] study on blood loss measurement. In a study conducted by KC Prasad and SC Prasad [1], it was shown that the older the child is, the greater the blood loss is.…”
Section: Discussionsupporting
confidence: 76%
“…Manual syringing of intravenous fluid may be desirable in three settings: first, if there is a need to control the volume tightly (e.g. in paediatric resuscitation) , secondly, if there is a need to use higher pressures to drive flow (e.g. with intra‐osseous devices) and thirdly, if it is necessary to introduce a small volume rapidly (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Se determinó un sangrado intraoperatorio promedio de 41 ml, algo menor a lo observado en otros estudios [7]- [9]. Hubo una gran dispersión a causa de Figura 1.…”
Section: Discussionunclassified
“…La literatura con respecto al sangrado intraoperatorio es limitada. En 1965, Holden et al, estimó dicho sangrado en 128,1 ml en pacientes de 4 a 12 años [7], mientras que estudios más recientes sugieren 92,46 ml [8] y 73,7-79,8 ml en pacientes de 4 a 9 años [9]. A pesar de ser potencialmente severo, la tasa de transfusión asociada al sangrado intraoperatorio se mantiene baja (0%-3%), y a menudo se ve relacionada con alteraciones de la coagulación [10], [11].…”
unclassified